Managing for Political Corporate Social Responsibility: New Challenges and Directions for PCSR 2.0 - Scherer, Andreas Georg; Rasche, Andreas; Palazzo, Guido; Spicer, André (Journal of Management Studies, 2016)
ABSTRACTThis article takes stock of the discourse on ‘political CSR’ (PCSR), reconsiders some of its assumptions, and suggests new directions for what we call ‘PCSR 2.0’. We start with a definition of PCSR, focusing on firms’ contribution to public goods. We then discuss historical antecedents to the debate and outline the original economic and political context. The following section explores emerging changes in the institutional context relevant to PCSR and reconsiders some of the assumptions underlying Habermas’ thesis of the postnational constellation. This highlights some neglected issues in previous works on PCSR, including the influence of nationalism and fundamentalism, the role of various types of business organisations, the return of government regulation, the complexity of institutional contexts, the efficiency of private governance, the financialization and digitalization of the economy, and the relevance of managerial sensemaking. Finally, we discuss the contributions to this special issue and relate them to the newly emerging research agenda.